Evaluación de nuevas fuentes de agua y mejora del acueducto de San Isidro de El Guarco, Cartago - Cordero-Retana, Marilyn Pamela (Instituto Tecnológico de Costa Rica, 2014)
The Aqueduct of San Isidro de El Guarco is in need of a immediate intervention due to water shortages during the dry season was presented in the catchments El Cubano, Casa Blanca #1 and Casa Blanca #2, the flow is insufficient to meet the demand during summer. New water sources near the population was proposed to achieve the maximum daily flow of 13 L / s is required over a period of 20 years. During rainy season, the increase of solid color and was in the water storage tank. The causes of the presence of high water turbidity and condition of slow upward flow filter were evaluated. The methodology used to afford data análisis was visits and interviews with the plumber and the manager of the ASADA were scheduled, in order to assess the current situation of the aqueduct; through the database SENARA, which two streams flow more was chosen to ensure the demand for current and future population needs. Each of the structures were measured internally, because there were no plans or the functioning of the chlorination was known and for 12 hours the volume change was measured in the storage tank for the use by users of San Isidro. The main results are that using the headwaters, the topographic profile of the pipe driving was obtained, this to ensure easy installation and lower costs. Also, with the high value of 12.95 NTU turbidity in the water filter in November indicates the status of the filter should be checked and constructing two filters to treat the flow entering the treatment plant. Expanding volume of 197 m3 is required in the storage tank. As finding in the months of December to April a decrease in precipitation is presented, as illustrated in the water balance, indicating a deficit of water in summer. Is recommended that the technical study, to determine whether the construction of a dam is the only technically feasible solution.
Proyecto de Graduación (Licenciatura en Ingeniería Ambiental) Instituto Tecnológico de Costa Rica, Escuela de Química, 2014.
Keywords: Acueductos; Tuberías; Desinfección; Almacenamiento; Tanques; Agua de lluvia